Existentialism and Its Influence on Our Understanding of Knowledge, Truth, Morality, Values, and Religion - John Michael Sasan (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
Existentialism is a philosophical movement that has had a significant impact on our understanding of knowledge, truth, morality, values, and religion. This research aims to explore the influence of existentialism on these fundamental aspects of human existence. The research methodology involved an extensive review of literature from prominent existentialist philosopher, Friedrich Nietzsche. The findings of this research highlight that existentialism challenges the traditional view of objective truth and knowledge, emphasizing the subjective and personal experience of individuals. Furthermore, existentialism posits that individuals must create their own values and meaning in life, rather than relying on external sources such as religion or society. In terms of morality, existentialism emphasizes the individual's responsibility for their actions, as opposed to being governed by universal ethical principles. The limitations of this research include the focus on Western existentialist philosophy, neglecting other cultural and philosophical traditions. The contribution of this research is that it sheds light on the influence of existentialism on various aspects of human existence and highlights the significance of subjective experience and personal responsibility. The practical implication of this research is that it provides insight into the importance of individualism and personal agency in various domains, such as education, mental health, and politics. The novelty of this research lies in the comprehensive exploration of existentialism's influence on various aspects of human existence, providing a unique perspective on these topics.